2018
DOI: 10.1002/jmrs.302
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cross‐sectional imaging in the management of suspected scaphoid fractures

Abstract: Cross-sectional imaging allows for faster scaphoid fracture diagnosis than X-ray. We propose a protocol for scaphoid fracture diagnosis wherein patients undergo two episodes of X-ray separated by 7 days, followed by a single MRI if clinical suspicion remains, minimising unnecessary immobilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…The study of Wijetunga et al [15] matches with our study results that CT and MRI have equal sensitivity to displaced and nondisplaced fractures. The study preferred MRI due to its reduced radiation risk.…”
Section: Discussionsupporting
confidence: 91%
“…The study of Wijetunga et al [15] matches with our study results that CT and MRI have equal sensitivity to displaced and nondisplaced fractures. The study preferred MRI due to its reduced radiation risk.…”
Section: Discussionsupporting
confidence: 91%
“…[37][38][39] This, together with the large number of false positives, implies that follow-up radiographs cannot be considered as a reference in the diagnosis of scaphoid fractures. 36,38,40,41 Interobserver agreement for MRI assessment of scaphoid fracture by four and five observers in cohorts of 79 and 64 patients, with a similar percentage of scaphoid fractures among those suspected clinically as in our study, was κ = 0.67 and κ = 0.44 respectively, representing moderate to substantial agreement. 42,43 Beeres et al, 44 in a study in which bone scans of both wrists of 100 patients with a clinically-suspected scaphoid fracture on at least one side were analyzed by three observers, found substantial agreement, κ = 0.61 to 0.80, for the diagnosis of a scaphoid fracture and for the diagnosis of other fractures.…”
Section: Discussionsupporting
confidence: 65%
“…A similar approach was recommended by Wijetunga et al in a study reported in the current issue of Journal of Medical Radiation Sciences. The authors conducted a retrospective review of patients with suspected scaphoid fractures presenting to an urban hospital.…”
mentioning
confidence: 84%